2018
DOI: 10.1001/jama.2018.0948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pediatric Early Warning System on All-Cause Mortality in Hospitalized Pediatric Patients

Abstract: clinicaltrials.gov Identifier: NCT01260831.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
185
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(205 citation statements)
references
References 35 publications
0
185
0
3
Order By: Relevance
“…A variety of PEWS tools have been described, and there is conflicting evidence regarding the impact of PEWS in high‐resource settings. Implementation of PEWS has been shown to reduce rates of cardiac and respiratory arrests outside of the PICU, unplanned PICU transfers, and the severity of illness at the time of PICU transfer as well as improve PICU use; however, a recent study failed to demonstrate an impact on hospital mortaliy . Although to our knowledge there are limited data regarding the impact of PEWS in resource‐limited settings, PEWS have been shown to reduce hospital mortality in settings with higher baseline mortality rates, as observed in hospitals with resource limitations or in high‐risk patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of PEWS tools have been described, and there is conflicting evidence regarding the impact of PEWS in high‐resource settings. Implementation of PEWS has been shown to reduce rates of cardiac and respiratory arrests outside of the PICU, unplanned PICU transfers, and the severity of illness at the time of PICU transfer as well as improve PICU use; however, a recent study failed to demonstrate an impact on hospital mortaliy . Although to our knowledge there are limited data regarding the impact of PEWS in resource‐limited settings, PEWS have been shown to reduce hospital mortality in settings with higher baseline mortality rates, as observed in hospitals with resource limitations or in high‐risk patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…This year marks the publication of the first prospective multicentre randomised controlled trial of PEWS 10. The Bedside PEWS are notable for the rigour of development and prior validation in differing populations 11 12.…”
Section: Where Are They Used and How Do They Perform?mentioning
confidence: 99%
“…Paediatric early warning scores (PEWS)-based assessment is thought to reduce the variability in this process. The EPOCH cluster randomised clinical trial compared the introduction of the 'bedside PEWS' to usual care in hospitalised children [10]. This large and impressive study showed that 'bedside PEWS' was not associated with a reduction in mortality.…”
Section: Paediatric Early Warning Scores (Pews)mentioning
confidence: 99%